Sistem Monitoring dan Deteksi Dini Pencemaran Udara Berbasis Internet Of Things (IOT) - Muhammad Hasanuddin; Herdianto Herdianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The problem of environmental pollution has been a concern for a long time and continues to be an important issue today. One form of pollution that is very detrimental is air pollution, which causes a decrease in air quality and disrupts its normal function. . The ISPU Scale usually consists of several categories that describe the level of air quality, such as the range 1-50 is said to be